Attitudes towards Information System Security among Physicians in Croatia - Markota, M.; Kern, J.; Švab, I. (Methods of Information in Medicine, 2001)
To examine attitudes about information system security among Croatian physicians a cross-sectional study was performed on a representative sample of 800 Croatian physicians. An anonymous questionnaire comprising 21 questions was distributed and statistical analysis was performed using a chi-square test. A 76.2% response rate was obtained. The majority of respondents (85.8%) believe that information system security is a new area in their work. In general, physicians are not informed about European directives, conventions, recommendations, etc. Only a small number of physicians use personal computers at work (29%). Those physicians who have a personal computer use it mainly for administrative reasons. Most health-care institutions (89%) do not have a security manual and the area of information system security is left to individual interest and initiative. Only 25% of physicians who have a personal computer use any type of password. A high percentage of physicians (22%) has never thought about the problem of personal data being used by organizations (e.g. police, banks) without legal background; a small, but still significant percentage of physicians (5.6%) has even agreed with such use. Results indicate that for the vast majority of physicians, information system security is a new area in their daily work, one which is left to individual interest and initiative. They are not familiar with the ethical, technical and legal backgrounds which have been defined for that area within the Council of Europe and the European Union. New aspects: This is the first study performed in Central and Eastern Europe dealing with information system security, performed on a representative nationwide sample of all the physicians.
Keywords: Information System Security; Attitudes; Survey